Examination of the Correlation Between Physical and Psychological Measures in Community-Dwelling Older Adults - Staples WH (Dove Medical Press, 2020)
William H Staples, Adam Kays, Rachel Richman Krannert School of Physical Therapy, University of Indianapolis, Indianapolis, IN, USACorrespondence: William H StaplesKrannert School of Physical Therapy, University of Indianapolis, 1400 East Hanna Avenue, Indianapolis, IN 46227, USATel +1 317-788-2112Fax +1 317-788-3542Email stapleswh@uindy.eduIntroduction: The purpose of this study was to determine if correlations exist between strength and mobility and psychological measures of anxiety and depression in community-dwelling older adults.Methods: One hundred and eleven participants randomly completed trials of grip strength (GS), the Timed Up and Go (TUG), the 10-meter walk test (10MWT), the Geriatric Anxiety Scale (GAS), and the Geriatric Depression Scale (GDS) in a prospective, correlational study.Results: This study found significant correlations between and within physical measures of strength and mobility and psychological measures. Age, GS, GDS, and education were significant predictors of gait speed (10MWT). Age, GS, and GDS were predictors of TUG scores. Grip strength was found to be a significant predictor of fall status; fallers had significantly weaker GS than non-fallers. Symptoms of anxiety (GAS) were predictive of symptoms of depression.Discussion: Objective measures of physical performance can provide information regarding an individual’s symptoms of anxiety and depression. Health professionals should understand the correlations between mood and physical ability to better treat their patients.Keywords: mood, mobility, older adults, falls